Progress in the Use of Biosourced Phenolic Molecules for Electrode Manufacturing - Quílez-Bermejo, Javier; Pérez-Rodríguez, Sara; Celzard, Alain; Fierro, Vanessa (Frontiers in Materials, 2022)
In the era of renewable technologies and clean processes, carbon science must adapt to this new model of a green society. Carbon materials are often obtained from petroleum precursors through polluting processes that do not meet the requirements of sustainable and green chemistry. Biomass is considered the only renewable source for the production of carbon materials, as the carbon in biomass comes from the consumption of carbon dioxide from the atmosphere, resulting in zero net carbon dioxide emissions. In addition to being a green source of carbon materials, biomass has many advantages such as being a readily available, large and cheap feedstock, as well as the ability to create unique carbon-derived structures with well-developed porosity and heteroatom doping. All these positive aspects position biomass-derived carbon materials as attractive alternatives in multiple applications, from energy storage to electrocatalysis, via adsorption and biosensors, among others. This review focuses on the application of phenolic resins to the production of electrodes for energy storage and the slow but inexorable movement from petroleum-derived phenolic compounds to biosourced molecules (i.e., lignins, tannins, etc.,) as precursors for these carbon materials. Important perspectives and challenges for the design of these biosourced electrodes are discussed.